Factors influencing passenger loyalty towards public transport services: does public transport providers’ commitment to environmental sustainability matter? - Vicente, P.; Sampaio, A.; Reis, E. (Case Studies on Transport Policy, 2020)
Public transport providers are constantly looking for ways to increase their ridership, either by gaining new or maintaining current passengers. In recent years, societies’ increasing concern about climate change and preserving the environment has led public transport providers in many countries to become more oriented towards environmental sustainability. The decision of transit agencies to become “greener” benefits the environment and may also benefit the business because companies that are able to visibly demonstrate their ethics and show a commitment to the environment are more likely to have a stronger reputation and attract customers who care deeply about what a business stands for. This study explores the impact of several factors on passenger loyalty towards public transport services. We use structural equation models (SEM) to explore the relationship among various constructs using data collected by means of a survey on public transit users in the Metropolitan Area of Lisbon (Portugal). In particular, we introduce the concept of Commitment to Environmental Sustainability (CES), which represents the contribution public transport providers make towards sustainable development and a cleaner environment and hypothesize that CES positively affects transit passengers’ loyalty. By comparing various SEM models, we find that the public transport providers’ commitment to environmental sustainability does have a direct positive effect on passenger loyalty and an indirect positive effect on loyalty when mediated by satisfaction. The managerial implications of the findings for the public transport service are addressed.